PROGRAM WIRAUSAHA (KRIPIK) DENGAN MEMANFAATKAN POTENSI LOKAL DI DESA KOMBAPARI KABUPATEN SUMBA TIMUR - Hariadi, Fajar; Enda, Riwa Rambu Hada; Jowa, Ngailu; Kudu, Yonski Umbu; Ndima, Indra Huki R.; Ndamung, Enjelita Pati; Chintika, Resni Ina; Kapu, Senli Rosiana; Lunga, Magdalena Tenga; Lero, Paschalis Risto Padi; Tamar, Debora Dembi; Pati, Ardon Umbu K.; Aprilia Kahi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Real Work Lectures (KKN) are a form of university students' service to the community through the provision of empowerment assistance, training, counseling, guidance, mentoring and to realize their potential, as well as helping to improve the quality of life and development. Observation was carried out by the following methods: (I) Visiting (2) Questions and answers, (3) Documentation, and (4) Looking at the field directly. The physical group programs are the Village Office Arrangement Program and Introduction, Devotional Work, Mutual Cooperation in the village office and in elementary schools, Procurement of garbage cans and the Making and Installation of RT/RW Planks, Chairmen of BPD, Posyandu, Hamlets (I and 2), Churches and PAUD and Basic Family Data Collection for the creation of village and entrepreneurial profiles. Meanwhile, the non-physical group program is Counseling for Making Chips Business Proposals and training on making chips. The potential of the community and the environmental conditions are very supportive for the holding of a flagship program which is hoped that this activity can continue with the support of the entire community. Judging from the program, students play the role of facilitators, dynamizers and motivators. Overall, all work programs were carried out according to plan. The success is seen from the number of participation and support of the Kombapari Village community in all activities. All activities can run well, it is evident from the public opinion in general. Thus, the residents of Kombapari Village can continue to develop their existing potential.